Biochemical Investigation of 3‐Sulfopropionaldehyde Reductase HpfD. (3rd September 2021) - An, Junwei; Wei, Yifeng; Liu, Jiayi; Lui Ang, Ee; Zhao, Huimin; Zhang, Yan
Abstract: Sulfoquinovose is the polar headgroup of plant sulfolipids and is a globally abundant organosulfur compound, and its degradation by bacteria is an important component of the sulfur cycle. Sulfoquinovose degradation by certain bacteria, including Escherichia coli, produces dihydroxypropanesulfonate (DHPS), which is further converted by anaerobic bacteria into 3‐hydroxypropanesulfonate (3‐HPS), through the catalytic action of DHPS dehydratase (a member of the glycyl radical enzyme family), and sulfopropionaldehyde reductase HpfD (a member of the metal‐dependent alcohol dehydrogenase family). Here we report biochemical investigation of Hungatella hathewayi HpfD. In addition to 3‐HPS, HpfD also displayed high catalytic activities for NAD + ‐dependent oxidation of 4‐hydroxybutanesulfonate (4‐HBS) and γ‐hydroxybutyrate (GHB). The highest activity was obtained with Fe 2+ or Mn 2+ as the divalent metal cofactor. Bioinformatics studies suggest that, in addition to DHPS degradation, 3‐HPS and γ‐aminobutyrate (GABA) degradations also involve HpfD homologs. Abstract : Sulfoquinovose is a globally abundant organosulfur compound. Degradation by communities of anaerobic bacteria produce 3‐hydroxypropanesulfonate, catalysed by sulfopropionaldehyde reductase HpfD. Biochemical investigation of HpfD revealed dehydrogenase activity for a range of alcohols, including 3‐hydroxypropanesulfonate, 4‐hydroxybutanesulfonate and γ‐hydroxybutyrate. Bioinformatics investigations suggest involvement of HpfD homologs in 3‐HPS and γ‐aminobutyrate degradation.